CONTRIBUTION TO ECONOMIC ANALYSIS OF CLIMATE CHANGE - Popov, Đorđe (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
Climate changes are global both in its causes and its consequences. Each action related to climate changes that has ambitions to be successful must be organized on a global level with full international cooperation and understanding. Those who are wealthier and bearing the greater responsibility for the high level of emissions those should take corresponding proportions in efforts to reduce emissions. There are three basic ways how to solve the economic problem of excessive emissions. The first is the taxation. The second is trade with the emission allowances. The third way is through the establishment of regulations and standards. Only measures, which include the right to sustainable development, can mobilize forces in the world that will lead the humanity, through long-term transition, in the post-fossil era.